KORELASI ANTARA EKSTRAKURIKULER DENGAN PENGEMBANGAN POTENSI SANTRI PUTRI AL MAHRUSIYAH I KEDIRI, JAWA TIMUR - Zaenal Arifin; Nala Rosida (Jurnal Ilmiah Didaktika, 2020)
This study discusses how the correlation between extracurricular activities and the development of psychological potential includes the talents and creativity of female students in Al Mahrusiyah I Kediri. Talent and creativity are very important and needed for someone to work and contribute to society. Therefore, people really need individual talent and creativity to help develop human civilization to become more advanced. This study uses correlational quantitative methods, with product-moment correlation data analysis techniques. Among the data collection techniques used in this study were questionnaires/questionnaires with a total sample of 33 santri. The results showed that the calculation of extracurricular activities reached 53% in the moderate or good enough category, and the calculation of potential development reached 78% or in the high or good category, while the calculation of the correlation between extracurricular and the development of potential students in the category of good or high was 0.713 with sig 0,00 this means that between extracurricular and potential development there is a significant relationship.